Significance of the tethered maxillary frenulum: a questionnaire-based observational cohort study - Sody A. Naimer; Ariel Israel; Aviezer Gabbay (The Korean Pediatric Society, 2021)
Background The clinical significance of lip-tie, or a tethered maxillary frenulum, remains under debate. Clinicians and parents are often perplexed when deciding whether procedures available to relieve a seemingly tight or severe maxillary frenulum are needed. Purpose No previous studies have assessed the consequences of not subjecting a tethered maxillary frenulum in newborns to surgical intervention. This study aimed to contribute the first prospective trial on this topic with a relatively extended followup of these newborn infants. Methods This prospective observational questionnaire-based cohort trial was performed in a community setting and aimed to determine whether lip-tie is associated with an increased likelihood of eventual feeding or oral disorders. Results The convenience sample comprised of 61 consecutively arriving infants with concomitant tethered frenula who were treated at the clinic for various reasons. This cohort was compared with a random sample of 66 age-matched children for a mean follow-up period of 6.42 years. Infants undergoing oropharyngeal procedures were excluded. Awareness of a deviation in oral structures was reported by 18% of the study group versus 0% of the controls. Mothers participating in the study group (24.6%) less frequently recalled painful nipples or discomfort during breastfeeding than those in the control group (47.0%) (P<0.01). There were no intergroup differences in other types of feeding difficulty, dental hygiene, pronunciation, or speech development. Conclusion Our findings suggest that a tethered labial frenulum is not associated with an increase in breastfeeding disturbances or oral disorders. These data encourage clinicians to question the need to intervene in cases of tethered maxillary frenula.